Who benefits from cognitive skills programs?: differential impact by risk and offense type - Travers, Rosie (Criminal justice and behavior, 2014)
Cognitive skills programs, which teach problem-solving skills and perspective taking, have a strong evidence base for their ability to reduce recidivism with convicted populations. This study explored whether the Enhanced Thinking Skills program, delivered over several years to 21,000 male prisoners in England and Wales, reduced reoffending for some categories of offenders more than others by comparing predicted with actual reconviction rates. Consistent with earlier research, attending the program was associated with significantly reduced reoffending for sexual offenders (a 13 percentage point reduction), violent offenders (17 point reduction), and other non-acquisitive offenders (10-12 points), but not for offenders convicted of burglary or robbery. After controlling for risk, age, previous offenses committed, sentence length, and program completion, current offense type persisted as an independent and significant predictor of reoffending. Implications for the targeting of cognitive skills programs from this evaluation of a real world, large-scale implementation, and directions for future research, are discussed.